A Study of Rachel Glass’s Earth Speaks Using Arran Stibbe’s Framing Metaphor to Foster Environmental Awareness - Sanam Habib; Aneela Anjum; Naima Noreen (`, 2025)
This research aims to analyze Rachel Glass’s poem Earth Speaks through Arran Stibbe’s Eco linguistic framework of metaphors (2015). Through the use of Arran Stibbe’s theoretical framework of Eco linguistic given in ‘Language, Ecology, and the Stories We Live By’ (2015) this study uncovers the poem’s multiple levels of meanings, framed through the use of metaphors and discovers its impending effect on readers’ insights of environmental issues. By employing a qualitative research approach rooted Arran Stibbe’s Eco linguistic framework (2015), the research interprets Rachel Glass’s poem “Earth Speaks” to illuminate her exploration of environmental concerns such as deforestation, pollution, and biodiversity damage. Through careful analysis, the study reveals Glass’s critique of environmental degradation, lament of ecological dilapidation, and advocacy for harmonious synchronicity with nature. Drawing on Stibbe’s Eco linguistic framework of metaphors, the study not only explores the intersections between the poem and environmental consciousness, but also highlights the power of use of metaphors in the poem to inspire environmental awareness and action. The poem “Earth Speaks” highlights how poetry may be used to fight for the future and increase ecological consciousness. This research discovers the ways in which Glass’s text engages with ecological themes, strongly depicted through the use of metaphors, in promoting environmental awareness. Keywords: Ecolinguistics, Arren Stibbe’s framework of metaphors, environmental themes, environmental issues, environmental awareness.